Enhanced fracture toughness of hierarchical carbon nanotube reinforced carbon fibre epoxy composites with engineered matrix microstructure. (20th January 2019) - Zainol Abidin, M. Shukur; Herceg, Tomi; Greenhalgh, Emile S.; Shaffer, Milo; Bismarck, Alexander
Abstract: Fibre reinforced hierarchical composites further reinforced with up to 25 wt% of carbon nanotubes (CNTs) were manufactured using a wet powder impregnation route. Microstructural heterogeneity in the matrix of these laminates was engineered during wet powder impregnation to produce CNTs rich regions with spatial separation. The Mode I fracture toughness of these heterogeneous hierarchical composites increased by 41% and 26% compared to that of baseline carbon fibre epoxy composites and hierarchical composites with homogeneously distributed CNTs throughout the matrix with similar CNT content, respectively. Increased crack path tortuosity was observed to contribute to this increase in fracture toughness. The interlaminar shear strength was unaffected by the matrix microstructural heterogeneity.